IMPROVING STUDENTS’ READING COMPREHENSION THROUGH GIVING QUESTION AND GETTING ANSWER AT THE TENTH GRADE OF SMA NEGERI 2 BULUKUMBA - Andi Anugrah M; Achyana Sulfiah (Jurnal Education and Development, 2020)
The research aimed at finding out the improvement of students’ reading comprehension by Giving Questions and Getting Answer (GQGA Strategy) at class X MIPA 4 of SMA Negeri 2 Bulukumba. This research used Giving Questions and Getting Answer (GQGA Strategy) applied in the class when the researcher taught the students of SMA Negeri 2 Bulukumba This research was classroom action research that consisted of two cycles. One cycle consisted of four meetings. It means that there were eight meeting in two cycles. This classroom action research was done at SMA Negeri 2 Bulukumba for Englishsubject. The findings of this research were the improvement of the students’ reading comprehension of narrative text in which the mean score of diagnostic test was 54,97 and the mean score of cycle I was 69,97. It means that the difference between score of D-test and C1-Test is 15. Then, the mean score of cycle II was 82,23. The result above indicated that there was significant improvement of the students’ reading comprehension through Giving Question and Getting Answer Strategy at class X MIPA 4 of SMA Negeri 2 Bulukumba.